Reduced Need of Infiltration Anesthesia Accompanied With Other Positive Outcomes in Diode Laser Application for Frenectomy in Children - Do Hoang, Viet; Vo Truong Nhu, Ngoc; Le Quynh, Anh; Le Hoang, Son; Chu, Dinh-Toi; Phung Thi Thu, Ha; Chu-Dinh, Thien (Journal of Lasers in Medical Sciences, 2019)
Introduction: The abnormal maxillary labial frenum is common in children during the primary or mixed dentition stage. A conventional surgery for this abnormality usually requires infiltration anesthesia which leads to fear in children and consequent noncooperation during the surgery. The aim of present study was to evaluate the reduction in the need of infiltration anesthesia, intraoperative bleeding control and postoperative pain and wound healing in children when using the diode laser for abnormal labial frenum in the maxilla. Methods: The present study was carried out among 30 children attending the Hanoi Medical University, Vietnam. A Diode Laser with 810 nm wavelength and power of 0.8 W was used for frenectomy. Results: The proportion of procedures without any need of infiltration anesthesia was 70%, while 93.34% of children demonstrated positive and very positive behavior. Proportion of indolence on the first day after surgery was 83.3%. While 83.3% of children did not take any analgesics, not a single child complained of any pain 3 days after surgery. Conclusion: Our results indicated that the use of diode laser showed several benefits in maxillary labial frenectomy in children. These included reducing the need of infiltration anesthesia, increasing the children’s cooperation as well as decreasing the postoperative pain.